Pengaruh Growth Mindset terhadap Kinerja Karyawan: Systematic Literatur Review - Dini Kusumawati; Arum Dwi Nurrohmah; Putri Adella Finata; Dani Rizana (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to analyze the influence of growth mindset on employee performance using a Systematic Literature Review (SLR) approach. A growth mindset is understood as the belief that an individual's abilities can continually develop through effort, appropriate strategies, and continuous learning processes. This concept has become increasingly relevant in modern organizational environments that are dynamic and highly competitive, making a deeper understanding of its impact essential for human resource development. The research method involves collecting, selecting, and analyzing scientific articles published between 2020 and 2025 that are directly related to growth mindset and employee performance. The review findings indicate that growth mindset consistently contributes positively to various performance indicators, such as productivity, creativity, resilience in facing challenges, adaptability to change, and work motivation. The results also reveal that variables such as self-efficacy, intrinsic motivation, training, and organizational support may act as mediators or moderators within this relationship. The theoretical and practical implications of this study provide valuable insights for management in designing employee development strategies based on mindset enhancement that support a growth-oriented organizational culture.